Pengaruh Trust dan Ethical Climate terhadap Affective Commitment dengan Employee Readiness for Change sebagai Variabel Mediasi pada PT. XYZ - Evilina Sjaiful; Herman Susilo; Altatif Dianawati (Economics and Digital Business Review, 2025)
This study aims to analyze the effects of trust and ethical climate on affective commitment, with employee readiness for change as a mediating variable among employees of PT. XYZ. The study adopts a quantitative approach with a causal research design. Primary data were collected through the distribution of questionnaires to 100 employees selected using a proportional random sampling technique. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with the SmartPLS software. The results indicate that trust has a positive and significant effect on affective commitment and employee readiness for change, while ethical climate has a positive and significant effect on employee readiness for change, but does not have a significant effect on affective commitment. Furthermore, employee readiness for change does not have a significant effect on affective commitment and does not mediate the relationship between trust or ethical climate and affective commitment. These findings emphasize that employee trust is a key factor in strengthening affective commitment and enhancing organizational readiness for change.